Reviewing the Development of Information, Service, and Website Quality towards Traveloka Customer Satisfaction in Indonesia - Epifania Kurnia Januarti; Denis Priantinah (Petra International Journal of Business Studies, 2018)
Traveloka is one of the solutions in providing the best service for consumers who want to travel between cities and countries. Traveloka users up to 2018 are quite numerous, but it is not yet known how far the quality is given in meeting consumer needs. This study aims to determine the extent of the quality of information systems from Traveloka in meeting the needs of the Indonesian people. The research method uses literature based on information obtained through the phenomena that occur today and previous research. The results of this literature study show that the quality of Traveloka in Indonesia is relatively good with some previous research results stating that the quality of information and services affects customer satisfaction. Other variables that influence are found on the quality of the website and payment system. This research contributes to giving customers an overview of Traveloka's quality that can be trusted and provides an overview for new business people in developing business in the field of tour & travel which are promising to date.